Asymptomatic pancreatitis associated with plozapine - Bergemann, Niels; Ehrig, Christian; Diebold, K.; Mundt, Christoph; Einsiedel, Regina W. von (Pharmacopsychiatry, 1999)
Thieme E-Books & E-Journals
Online veröffentlicht: 20. April 2007
Online 20. April 2007
Gesehen am 16.12.2020